Evolution in the intellectual structure of BIM research: a bibliometric analysis - Olawumi, Timothy O.; Chan, Daniel W. M.; Wong, Johnny K. W. (Journal of Civil Engineering and Management, 2017)
Building Information Modelling (BIM) processes have continued to gain relevance in the Architectural, Engineering, and Construction (AEC) industry with more resources directed toward it. This study conducts a bibliometric analysis of 445 BIM articles to investigate and understand the pattern of BIM research which include defining BIM research categories, evaluating the project sectors that are influenced by BIM, and tracking the funding structure of BIM research. A network map that displays a visualization of the structure of BIM literature by research origin, funding structure and geographical scope was designed. None of the previous reviews of literature analyzed the BIM articles’ corpus to such level and depth. The findings revealed research categories such as construction and project management and BIM learning, adoption & practice as the core research areas in BIM and highlighted trending research themes in BIM research. Authors based in Asia and Europe received more research grants than their counterparts in other regions; likewise, two-third of the articles was authored by academics in the United States, Korea, and the United Kingdom. The study provides its readers with relevant research areas that require considerations, and the discussion of selected research areas provides an extensive understanding of salient BIM fields.